2018
DOI: 10.1039/c8ta07273f
|View full text |Cite
|
Sign up to set email alerts
|

Pathways towards high performance Na–O2 batteries: tailoring graphene aerogel cathode porosity & nanostructure

Abstract: Fundamental understanding of the physical phenomena and electrochemical reactions occurring in metalair batteries is critical for developing rational approaches towards high-performing Na-O 2 battery cathodes. In this context, air cathode porosity plays a key role in battery performance, influencing oxygen supply and hence oxygen reduction and evolution reaction kinetics (ORR/OER). Graphene-based aerogels offer great versatility as air-cathodes due to their low density, high electronic conductivity and adjusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 44 publications
8
55
0
Order By: Relevance
“…5c. The isotherm of CNF presents a typical type-IV (IUPAC 1985) behavior with a H3-type hysteresis loop at relative pressure P/P 0 from 0.45 to 1.0, indicating the existence of narrow channel and meso/macropores, which agrees well with the TEM results [33,34] , indicating the sulfur almost completely penetrates into the porous structure of the CNF during the melt-diffusion process. As the MnO 2 content increases, the specific surface area of CNF@S/ MnO 2 -1, CNF@S/MnO 2 -2 and CNF@S/MnO 2 -3 increases from 88, 140 to 186 m 2 g −1 , respectively.…”
Section: Characterizations Of the Cnf@s/mnosupporting
confidence: 82%
“…5c. The isotherm of CNF presents a typical type-IV (IUPAC 1985) behavior with a H3-type hysteresis loop at relative pressure P/P 0 from 0.45 to 1.0, indicating the existence of narrow channel and meso/macropores, which agrees well with the TEM results [33,34] , indicating the sulfur almost completely penetrates into the porous structure of the CNF during the melt-diffusion process. As the MnO 2 content increases, the specific surface area of CNF@S/ MnO 2 -1, CNF@S/MnO 2 -2 and CNF@S/MnO 2 -3 increases from 88, 140 to 186 m 2 g −1 , respectively.…”
Section: Characterizations Of the Cnf@s/mnosupporting
confidence: 82%
“…The peak at À20 ppm could also be relatedt oN aO 2 .P revious publications by Liu et al [35] and Enterríae tal. [9] assign NMR peaks corresponding to NaO 2 at À27 and À25 ppm, respectively.T hese differences can be attributed to different electrolytes being used in the studies, which werep erformed by using glyme-based electrolytes, whereas the presentw ork focuses on ionic liquid-based electrolytes so thatt he 23 Na environmentsmay be different in the two cases.…”
Section: The Nature Of Discharge Productsmentioning
confidence: 99%
“…), the surface area is not the only factor that influences the overall battery performance but also the pore size and the electrode composition must be considered. [6][7][8][9] For instance, Chervin et al [6] studied the influence of the pore size on Li-oxygen batteries based on af ree-standing, carbon binder-free nanofoam cathode,a nd demonstrated that, althought he macroporous nanofoam hadl ower specifics urface area, it achieved higher discharge capacity than the mesoporousnanofoams.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 For example, with a view to its use as a cathode in M-O2 batteries, processing graphene into suitable three-dimensional porous architectures having well-interconnected nanosheets is expected to be advantageous, since an efficient electron transport, an unimpeded access of ions and gas molecules as well as a proper accommodation of the discharge products throughout the electrode can be simultaneously attained with such architectures. 4,12 These requirements can in principle be met by using graphene foams or aerogels obtained by chemical vapor deposition (CVD) techniques that employ metal (e.g., Ni) foams acting both as a catalyst and template. 4,13,14 Unfortunately, the high temperatures and controlled synthesis atmospheres usually associated to such techniques, together with the need to remove the metal template after the synthesis step, make the CVD approach expensive and difficult to scale up.…”
Section: Introductionmentioning
confidence: 99%